Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the distance between the points [tex]\((4, 6)\)[/tex] and [tex]\((7, -3)\)[/tex], we use the distance formula, which is defined as:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Here, [tex]\((x_1, y_1) = (4, 6)\)[/tex] and [tex]\((x_2, y_2) = (7, -3)\)[/tex].
Let's proceed step-by-step:
1. Calculate the difference in the [tex]\(x\)[/tex]-coordinates:
[tex]\[ x_2 - x_1 = 7 - 4 = 3 \][/tex]
Then square this difference:
[tex]\[ (x_2 - x_1)^2 = 3^2 = 9 \][/tex]
2. Calculate the difference in the [tex]\(y\)[/tex]-coordinates:
[tex]\[ y_2 - y_1 = -3 - 6 = -9 \][/tex]
Then square this difference:
[tex]\[ (y_2 - y_1)^2 = (-9)^2 = 81 \][/tex]
3. Sum these squared differences:
[tex]\[ (x_2 - x_1)^2 + (y_2 - y_1)^2 = 9 + 81 = 90 \][/tex]
4. Take the square root of the sum to get the distance:
[tex]\[ \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} = \sqrt{90} \approx 9.4868 \][/tex]
Given the provided multiple-choice options, the correct expression that matches our calculations and gives the distance is:
[tex]\[ \text{Option B: } \sqrt{(4-7)^2 + (6+3)^2} \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{\sqrt{(4-7)^2 + (6+3)^2}} \][/tex]
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Here, [tex]\((x_1, y_1) = (4, 6)\)[/tex] and [tex]\((x_2, y_2) = (7, -3)\)[/tex].
Let's proceed step-by-step:
1. Calculate the difference in the [tex]\(x\)[/tex]-coordinates:
[tex]\[ x_2 - x_1 = 7 - 4 = 3 \][/tex]
Then square this difference:
[tex]\[ (x_2 - x_1)^2 = 3^2 = 9 \][/tex]
2. Calculate the difference in the [tex]\(y\)[/tex]-coordinates:
[tex]\[ y_2 - y_1 = -3 - 6 = -9 \][/tex]
Then square this difference:
[tex]\[ (y_2 - y_1)^2 = (-9)^2 = 81 \][/tex]
3. Sum these squared differences:
[tex]\[ (x_2 - x_1)^2 + (y_2 - y_1)^2 = 9 + 81 = 90 \][/tex]
4. Take the square root of the sum to get the distance:
[tex]\[ \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} = \sqrt{90} \approx 9.4868 \][/tex]
Given the provided multiple-choice options, the correct expression that matches our calculations and gives the distance is:
[tex]\[ \text{Option B: } \sqrt{(4-7)^2 + (6+3)^2} \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{\sqrt{(4-7)^2 + (6+3)^2}} \][/tex]
Answer:
B. \(√((4-7)^2 + (6+3)^2)\)
Step-by-step explanation:
To find the distance between two points we use the distance formula:
sqrt( ( x2-x1) ^2 + ( y2-y1) ^2)
sqrt( ( 4-7) ^2 + ( (6--3) ^2)
sqrt( ( 4-7) ^2 + ( (6+3) ^2)
√((4-7)^2 + (6+3)^2)
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.